Malaysian Youth’s Quality of Life: Looking from the Perspective of Eating Behaviour - Delicious, Dynatalie; Chik, Chemah Tamby; Jipiu, Lovelyna Benedict (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
The purpose of this study is to identify the relationship between eating behaviour and quality of life among youth in Malaysia. The systematic literature review and thematic content analysis initiated in Scopus, Web of Science, Science Direct, and PubMed published from 2018 to 2022 were reviewed. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards were followed for conducting the systematic review. A set of inclusion and exclusion criteria was used to identify relevant research, and data extraction and analysis were done to investigate the relationships. The study quality was assessed using the